Analysis of the Welfare of the Fisherman Community of Sibolga City (Comparative Study of Traditional Fishermen and Modern Fishermen) - Atmaja, Adithya Rahman; Lubis, Irsyad; Sari, Raina Linda (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The research findings indicate several distinctions in the well-being levels between modern and traditional fishermen in Sibolga City across various indicators. Firstly, a notable disparity exists in income and consumption indicators. Modern fishermen exhibit significantly higher well-being percentages (92.56%) categorized as highly prosperous (SS), while traditional fishermen score at a moderately prosperous level (58.64% - CS). This difference is supported by the Kruskal-Wallis test (Asymp. Sig. = 0.044 < 0.05), confirming the divergence in well-being between traditional and modern fishermen based on income and consumption. Second, no significant difference is observed in living conditions between modern and traditional fishermen. Both groups show high well-being percentages; modern fishermen at 99.30% (SS) and traditional fishermen at 90.99% (SS), supported by the Kruskal-Wallis test (Asymp. Sig. = 0.235 > 0.05), indicating a lack of disparity in well-being based on residential conditions. Thirdly, differences in the health status of family members indicate varied well-being levels between modern and traditional fishermen. Modern fishermen have a well-being percentage of 88.19% (SS), whereas traditional fishermen score at 78.49% (S). The Kruskal-Wallis test (Asymp. Sig. = 0.012 < 0.05) reinforces this disparity in well-being based on family health indicators. Lastly, disparities are found in educational accessibility indicators. Modern fishermen show significantly higher well-being percentages (97.08% - SS) compared to traditional fishermen (70.25% - S), backed by the Kruskal-Wallis test (Asymp. Sig. = 0.000 < 0.05), indicating distinct well-being levels between the two groups based on educational accessibility.